Efektivitas problem based learning dalam pembelajaran bahasa indonesia: analisis kuasi-eksperimen dengan motivasi belajar sebagai kovariat - Sari, Ni Wayan Lilia; Agung Gede Agung, Anak; Luh Gede Erni Sulindawati, Ni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The research employed a quantitative approach using a quasi-experimental design, specifically a non-equivalent control group design. The experimental group received instruction using the PBL model, while the control group was taught using a conventional teaching approach. Data were collected using a standardized Indonesian language achievement test developed based on curriculum indicators. The instrument underwent content validation by subject-matter experts and was empirically tested to establish construct validity and reliability, yielding a satisfactory reliability coefficient. Prior to hypothesis testing, prerequisite analyses including tests of normality, homogeneity, and linearity were conducted. The data were analyzed using an independent samples t-test and Analysis of Covariance (ANCOVA) to control for the influence of learning motivation. The findings revealed a statistically significant difference in learning achievement between students taught using the PBL model and those taught using conventional instruction (p < 0.05). After controlling for learning motivation, the ANCOVA results confirmed that the PBL model had a significant positive effect on Indonesian language achievement. These results indicate that PBL is more effective than conventional learning approaches in enhancing students’ academic performance. The study contributes theoretically by strengthening empirical evidence on the role of constructivist-based instructional models in language learning while accounting for motivational factors. Practically, the findings suggest that integrating PBL into Indonesian language instruction can improve not only academic achievement but also foster critical thinking and problem-solving skills. Therefore, PBL is recommended as an alternative instructional model to enhance the quality of Indonesian language education at the junior secondary level.